1994
DOI: 10.1084/jem.180.6.2113
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a 24-kD protease from apoptotic tumor cells that activates DNA fragmentation.

Abstract: SummaryWe report the purification of a protease from tumor cells undergoing apoptosis that is involved in activating DNA fragmentation. Initial studies revealed that two inhibitors of serine proteases, N-l-tosylamide-2-phenylethylchloromethyl ketone and carbobenzoxy-Ala-Ala-borophe (DK120), suppressed tumor necrosis factor or ultraviolet (UV) light-induced DNA fragmentation in the U937 histiocytic lymphoma as well as UV light-induced DNA fragmentation in the BT-20 breast carcinoma, HL-60 myelocytic leukemia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 46 publications
2
53
0
2
Order By: Relevance
“…Previous reports have suggested the implication of serine proteases in apoptosis induced by TNF and UV, 43,44 dexamethasone, 45 hypoxia reoxygenation, 46 DNA damage, 47 NGF deprivation 48 and the overexpression of s-Myc and cMyc. 49 Moreover, serine proteases were shown to play roles in the cleavage of chromatin into 50-300 kb pieces, 45 the activation of an endonuclease, 50 the processing of caspase-2 48 and caspase-3 44 and the cytochrome c-mediated activation of caspase-9.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested the implication of serine proteases in apoptosis induced by TNF and UV, 43,44 dexamethasone, 45 hypoxia reoxygenation, 46 DNA damage, 47 NGF deprivation 48 and the overexpression of s-Myc and cMyc. 49 Moreover, serine proteases were shown to play roles in the cleavage of chromatin into 50-300 kb pieces, 45 the activation of an endonuclease, 50 the processing of caspase-2 48 and caspase-3 44 and the cytochrome c-mediated activation of caspase-9.…”
Section: Discussionmentioning
confidence: 99%
“…The results are the average of three independent experiments several caspases and vigorously induces apoptosis (Stennicke and Salvesen, 1999). Several other proteinases including the cysteine proteinase, calpain, apoptotic serine proteinase p24 and cathepsin D have also been shown to be involved in apoptosis (Squier et al, 1994;Wright et al, 1994;Deiss et al, 1996;Hirsch et al, 1998;Nakagawa and Yuan, 2000). Our results demonstrated that at 0.1 mM DOX, PR3-mediated DOX-induced apoptosis in HL-60 cells was independent of the caspase-8 and -9 pathways, but was associated with the cleavage of caspase-3 in HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ICE-like proteases degrade lamins during apoptosis and may thereby trigger collapse of the chromatin [23,24]. A partially characterised 24-kDa protease has been shown to induce DNA degradation characteristic of apoptosis when added to purified nuclei possibly by activating an endonuclease as it does not itself exhibit any nuclease activity [25]. Activated CPP32/Yama or apopain can cleave poly-(ADP-ribose) polymerase (PARP) and thereby inhibit most of its DNA repair activity [11,12,18,19,26].…”
Section: Introductionmentioning
confidence: 99%